SEMANGKA SEBAGAI SIMBOL PERJUANGAN RAKYAT PALESTINA - Madaniyyah, Khaulah Tsabita; Letmiros, Letmiros (Multikultura, 2025)
This study aims to analyze how the watermelon is used, interpreted, and disseminated as a symbol of resistance and a form of expression of solidarity with the Palestinian struggle on social media. The research employs a descriptive qualitative approach through various literature sources. It draws upon Roland Barthes’ (1977) theory of signs and meaning to examine the symbolic use of the watermelon in this context. The findings reveal that the watermelon, whose internal colors resemble those of the Palestinian flag—green (rind) symbolizing resilience, white (inner rind) symbolizing sincerity, red (flesh) symbolizing courage, and black (seeds) symbolizing the emerging younger generation—has evolved into a powerful emblem of solidarity and resistance against Israeli oppression of the Palestinian people. The popularity of the watermelon as a symbol has grown significantly since the escalation of the Israel–Palestine conflict on October 7, 2023, up to the time this study was conducted. It has appeared in a variety of visual content formats, including emojis and TikTok filters, thereby broadening its symbolic reach and amplifying its impact on the global solidarity movement.